Analytical geometry and vector analysis - Pande H.D. Khan M.Q., Gupta B.N. and others (Dominant Pub., New delhi, 2000)
Biology/Zoology
UGC X PLAN (2004-2005)
ENGLISH
Keywords: Analytical geometry and vector analysis; Biology/Zoology; Biology/Zoology